Peran Liga Arab terhadap Konflik Palestina dan Israel - Muhammad Diawan Masri (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2022)
This study aims to see the world view of the two poets towards the Arab League on the conflict between Palestine and Israel, and how the role of the Arab League in the conflict between Palestine and Israel. The method used in this research is descriptive qualitative approach, with the type of library research. There are two types of data sources in this study, namely primary and secondary sources. The primary data sources were taken from the poem entitled